Effect of Replacing Fish Oil with Palm Oil on Liver Histology and Nutritional Quality of Nile Tilapia (Oreochromis niloticus) - Ayisi, Christian Larbi; Zhao, Jin-Liang (Indian Journal of Animal Nutrition, 2018)
The effects of replacing fish oil (FO) with palm oil (PO) in diets of Nile tilapia (Oreochromis niloticus)were studied on liver morphology as well as nutritional quality. An eight week feeding trial was conducted using five iso-nitrogenous and iso-caloric diets containing 0, 25, 50, 75 and 100% PO in replacement of FO. Each diet was randomly assigned to triplicate groups of 40 fishes. After 8 weeks of feeding trial, the findings demonstrated that body composition as well as liver and muscle lipid were not affected by different PO levels in diets. However, there was an increase (P<0.05) in liver lipids. Mean polyene index in groups fed 25, 50, 75 and 100% PO increased (P<0.05) compared with control group fed 0% PO. Fish fed higher levels of PO (75 and 100% PO) had higher (P<0.05) mean index of atherogenicity (AI) and thrombogenicity (TI) in the muscle. In the liver, fish fed 25% PO had the highest AI and TI values. Replacing FO with PO had effects on liver morphology. Hepatocytes as well as pancreatic acini were influenced by dietary lipid source. Therefore, a higher inclusion level of the PO induced negative effects on nutritional quality and liver morphology.